Baseline Clinical and Blood Biomarkers in Patients With Preataxic and Early-Stage Disease Spinocerebellar Ataxia 1 and 3. (25th April 2023) - Tezenas du Montcel, Sophie; Petit, Emilien; Olubajo, Titilayo; Faber, Jennifer; Lallemant-Dudek, Pauline; Bushara, Khalaf; Perlman, Susan; Subramony, Sub H.; Morgan, David; Jackman, Brianna; Paulson, Henry Lauris; Öz, Gülin; et al.
Abstract : Background and Objectives: In spinocerebellar ataxia, ataxia onset can be preceded by mild clinical manifestation, cerebellar and/or brainstem alterations, or biomarker modifications. READISCA is a prospective, longitudinal observational study of patients with spinocerebellar ataxia type 1 (SCA1) and 3 (SCA3) to provide essential markers for therapeutic interventions. We looked for clinical, imaging, or biological markers that are present at an early stage of the disease. Methods: We enrolled carriers of a pathologic ATXN1 or ATXN3 expansion and controls from 18 US and 2 European ataxia referral centers. Clinical, cognitive, quantitative motor, neuropsychological measures and plasma neurofilament light chain (NfL) measurements were compared between expansion carriers with and without ataxia and controls. Results: We enrolled 200 participants: 45 carriers of a pathologic ATXN1 expansion (31 patients with ataxia [median Scale for the Assessment and Rating of Ataxia: 9; 7–10] and 14 expansion carriers without ataxia [1; 0–2]) and 116 carriers of a pathologic ATXN3 expansion (80 patients with ataxia [7; 6–9] and 36 expansion carriers without ataxia [1; 0–2]). In addition, we enrolled 39 controls who did not carry a pathologic expansion in ATXN1 or ATXN3 . Plasma NfL levels were significantly higher in expansion carriers without ataxia than controls, despite similar mean age (controls: 5.7 pg/mL, SCA1: 18.0 pg/mL [ p < 0.0001], SCA3: 19.8 pg/mL [ p < 0.0001]). Expansion carriers without ataxia differed from controls by significantly more upper motor signs (SCA1 p = 0.0003, SCA3 p = 0.003) and by the presence of sensor impairment and diplopia in SCA3 ( p = 0.0448 and 0.0445, respectively). Functional scales, fatigue and depression scores, swallowing difficulties, and cognitive impairment were worse in expansion carriers with ataxia than those without ataxia. Ataxic SCA3 participants showed extrapyramidal signs, urinary dysfunction, and lower motor neuron signs significantly more often than expansion carriers without ataxia. Discussion: READISCA showed the feasibility of harmonized data acquisition in a multinational network. NfL alterations, early sensory ataxia, and corticospinal signs were quantifiable between preataxic participants and controls. Patients with ataxia differed in many parameters from controls and expansion carriers without ataxia, with a graded increase of abnormal measures from control to preataxic to ataxic cohorts. Trial Registration Information: ClinicalTrials.gov NCT03487367.